Epidemiological trends and direct costs of diabetes in a Northern Italy area: 2012 health administrative records analysis LHT n. 20 Verona. Issue 6 (December 2017) - Demurtas, J.; Alba, N.; Rigon, G.; Nesoti, M.V.; Bovo, C.; Vaona, A.
Highlights: Diabetes costs in the next future will be a major concern for Italian NHS. ACG is an applicable tool to analyze chronic diseases in the Italian setting. ACG could be useful to prioritize future research and assess interventions. Italian health administrative data need integration with primary care records. Abstract: Objective: This analysis estimates type 1 and type 2 diabetes direct costs in 2012, in terms of hospital care, outpatient visits, diagnostics and medications, in a local healthcare trust in Northern Italy (ULSS n.20 Verona). Methods: The Johns Hopkins Adjusted Clinical Group (ACG ® ) System was used to analyze data, including hospital discharges, emergency room admissions, medical encounter records, disease registries, copayment exemptions, home care services, psychiatric services, rehabilitation services, and medications. Data from general practitioners and nursing homes were not directly available. Patients obtained from the first analysis were subsequently divided in two groups (type 1 and type 2 diabetes) according to ATC drug classification system and age. Costs were estimated from inpatient and outpatients fees and drugs costs. Results: ULSS n. 20 takes care of about 480.000 people. We identified 974 people affected by type 1 diabetes (prevalence 0, 2%) and 24.087 people affected by type 2 diabetes (prevalence 5, 0%) among the residents in 2012. Hospitalization mean annual cost was 4.753, 50€ (SD 9.330, 19€) for type 1 diabetes and 1.718, 08€ (SD 5.087, 34€) for type 2 diabetes. Outpatient care mean annual cost was 1.401, 76€ (SD 4.394, 88€) for type 1 diabetes and 669, 15€ (SD 2.121, 24€) for type 2 diabetes. Medications mean annual cost was 1, 369, 35€ (SD1.781, 18€) for type 1 diabetes and 874, 07€ (SD 2.832, 2€) for type 2 diabetes. Conclusions: ACG ® diabetes data analysis agrees with data obtained by more expensive methods and seems to be a comprehensive and applicable tool to analyze chronic diseases dynamics in the Italian setting in order to prioritize future research and analyze the effects of interventions aimed to ensure the sustainability of public health services. Because of the combination between prevalence data and epidemiological trends, we could be at the eve of a dramatic increase of diabetes costs with major concerns for the Italian NHS ability to withstand.